Kitty's house of horrors eaudiobook - Vaughn, Carrie (Kitty Norville, 2010)
Talk radio host and werewolf Kitty Norville has agreed to appear on TV's first all-supernatural reality show. She's expecting cheesy competitions and manufactured drama starring shapeshifters, vampires, and psychics. But what begins as a publicity stunt will turn into a fight for her life. The cast members, including Kitty, arrive at the remote mountain lodge where the show is set. As soon as filming starts, violence erupts and Kitty suspects that the show is a cover for a nefarious plot. Then the cameras stop rolling, cast members start dying, and Kitty realizes that she and her monster housemates are the ultimate prize in a very different game. Stranded with no power, no phones, and no way to know who can be trusted, she must find a way to defeat the evil closing in before it kills them all.